2016
DOI: 10.1073/pnas.1600936113
|View full text |Cite
|
Sign up to set email alerts
|

The PSI–U1 snRNP interaction regulates male mating behavior in Drosophila

Abstract: Alternative pre-mRNA splicing (AS) is a critical regulatory mechanism that operates extensively in the nervous system to produce diverse protein isoforms. Fruitless AS isoforms have been shown to influence male courtship behavior, but the underlying mechanisms are unknown. Using genome-wide approaches and quantitative behavioral assays, we show that the P-element somatic inhibitor (PSI) and its interaction with the U1 small nuclear ribonucleoprotein complex (snRNP) control male courtship behavior. PSI mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 40 publications
(49 reference statements)
1
41
0
Order By: Relevance
“…Genome-wide analysis of differentially spliced mRNAs was performed using the Junction Usage Model (JUM) package 44,45 (https://github.com/qqwang-berkeley/JUM; version 1.3.2) with default parameters and following the JUM manual. Briefly, RNA-seq data were mapped to the Drosophila genome (dm3) using STAR 46 in two-pass mode, following instructions in the STAR manual (https://github.com/alexdobin/STAR).…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide analysis of differentially spliced mRNAs was performed using the Junction Usage Model (JUM) package 44,45 (https://github.com/qqwang-berkeley/JUM; version 1.3.2) with default parameters and following the JUM manual. Briefly, RNA-seq data were mapped to the Drosophila genome (dm3) using STAR 46 in two-pass mode, following instructions in the STAR manual (https://github.com/alexdobin/STAR).…”
Section: Methodsmentioning
confidence: 99%
“…Like FUBP1, Psi also interacts with RNA Pol II transcriptional machinery, particularly the transcriptional Mediator (MED) complex, to pattern Myc transcription, cell and tissue growth in the Drosophila wing epithelium (Guo et al, 2016). In addition to roles in transcription, Psi binds RNA via the KH domains and interacts with the spliceosome to regulate mRNA splicing (Labourier et al, 2001;Wang et al, 2016). Although Co-IP Mass Spectrometry detected Psi in complex with the Argonaute protein, AGO1 (Guo et al, 2016), the potential significance of this interaction is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…42 Indeed, subsequent studies revealed broader roles for Psi in pre-mRNA splicing, including for many genes required for male courtship behavior. 43 Further to these RNA processing functions, and in accordance with Psi behaving in a functionally analogous manner to FUBP1, recent studies revealed a key role for Psi in sustaining developmentally regulated MYC transcription and, thus, cell and tissue growth. 5 Moreover, like FUBP1, 44 Psi has potent transcriptional activator capacity in vitro, mediated by conserved tyrosine-rich domains (YM1 and YM2 repeats).…”
Section: Drosophila Fubp1/psi Interacts With Mediator To Control Tissmentioning
confidence: 94%